Three phase voltage source inverters with grid connected industrial application - N, Prakash; V.R., Balaji (International Journal of Engineering and Technology, 2018)
The grid-connected issue is one of the major problems in the field of Power Electronics. In this paper, the Three Phase Voltage Source Inverter (VSI) is controlled by a Space Vector Pulse Width Modulation (SVPWM) Technique. SVPWM control technique and Park transformation, the managed inverter control system to convert input DC power into AC power, stabilize the output voltage and current, and feeds the excess power to the utility grid can be achieved by controllers. Usually, the grid source contains higher level of harmonics. To analyze the harmonics, nonlinear load is connected externally in the point of common coupling. The main aim of this paper is to modeling, simulation and experimental study of the three-phase grid connected inverter. By using the control algorithm, the grid sides Total Harmonics Distortion (THD) are controlled to the 1.54% for 800V DC as per the IEEE standard. The stimulation results such as AC output voltage and current, inverter system power flow, and grid disturbances detection signals, proves the effectiveness of the developed control algorithm. The control algorithms to makes the for this inverter outputs is pure sinusoidal.